LEGAL ARGUMENTATION & LEGAL REASONING - Fontian Munzil (Media Nusantara, 2014)
The logic learn something such as the principles rules and procedures for correct of reasoning. Reasoning is the human thought process which generates a new statement sequentially which is the result of another statement that has been known previously. Logically formal truth relying on the existence of roads, ways, techniques and laws that be followed, then be analysed and finally formulated in a logical. Thinking is the object of that is the processing logical of reason to obtain the truth in a way consideration, describing, comparing and connects one understanding to another understanding. Legal Reasoning Methods provide rebuttal in disputed legal paradigm referred specifically to the application and implementation of the law. Legal Reasoning process required to maintain a legal action within the corridor of applicable law. Fallacy of reasoning occurred because there was no logical relationship p between the premise and conclusion and a violation of the rules of logical. Legal Reasoning looking for a basis of legal action. Legal reasoning is useful in finding the base to determine whether an incident has met all of the legal provisions of the law and the rules of law.